Nonreligious Self-Transcendent Experiences Occurred in Religious Contexts: A Reflection on Religion, Science, and Human Potential - Nguyen, Linh Thi Thuy (Religions, 2025)
Self-transcendence has been extensively studied and discussed among scholars, both theoretically and empirically. However, further academic inquiry into self-transcendent experiences (STEs), particularly their nature, religious implications, and spiritual benefits, is still needed. This paper undertakes a qualitative exploration of the topic, phenomenologically analyzing the author’s first-person STEs within Buddhist and Christian contexts. In addition to personal journals and reflections, the dataset includes email exchanges with and reports to supervisors, as well as comparative insights drawn from testimonies shared by individuals of various religious backgrounds. The findings suggest that while religion may sometimes inhibit its adherents from experiencing STEs, it can also serve as a catalyst for such experiences among nonreligious individuals. Furthermore, the universal nature of STEs, which transcends cultural and religious boundaries, has the potential to promote interfaith dialogue and provide a theoretical framework for fostering religious harmony. Data on STEs could also act as a bridge connecting science with other forms of human knowledge, enabling shared discourse and offering a complementary perspective for understanding the world. Finally, a proposed mechanism of STEs highlights their role in achieving lifelong peace by balancing physical and mental needs, while also offering insights to help individuals maximize their potential and lead fulfilling lives.